Critical Study of Persian Translation of the Routledge History of Philosophy: Renaissance and Seventeenth-century Rationalism - Majid Sadrmajles (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the present essay the Persian translation of Routledge History of Philosophy: Renaissance and Seventeenth-century Rationalism is reviewed. This work is volume 4 of the ten ones and was first published in 1993 by Routledge Publications. The editor of this book is J. R. A. Parkinson and the  Persian translator of the book is Seyyed Mostafa Sharaeeni with the editorship of Hassan Fathi. It was  first published in 1392 in Iran.After a brief introduction of the English text, our article is divided into two parts: 1- Reviewing  the formal aspects of the Persian translation, and 2- Reviewing  the material aspects. For both aspects, we compare some pages of Persian translation with the original text at random. Our relative conclusion reveals that the Persian translation is credible, understandable, and useful for Iranian students of philosophy. Experience and expertise of Persian translator and his attention to the philosophical terms are mainly from factors that make his translation  an academic reliable work. Of course, there are some unwanted slips the correction of which depicts ethical tasks and philosophical originality of translator against readers.